Electron-exchange-assisted photon energy up-conversion in thin films of π-conjugated polymeric composites - Keivanidis, Panagiotis E.; Laquai, Frédéric; Robertson, Joseph W.F.; Baluschev, Stanislav; Jacob, Josemon; Müllen, Klaus; Wegner, Gerhard (My University, 2011)
The mechanism of triplet-triplet annihilation (TTA)-induced up-converted (UC) delayed luminescence is studied in two different binary organic systems consisting of platinum(II) octaethyl porphyrin (PtOEP) mixed with either poly(fluorene) (PF26) or ladder-type pentaphenylene (L5Ph). Cyclic voltammetry and differential pulse voltammetry are employed for estimating the ionization potentials of PtOEP and L5Ph. Delayed luminescence spectroscopy sets the energy of the lowest excited triplet state of L5Ph 0.20 eV higher than the triplet state of PtOEP (1.90 eV). The different phosphorescence PtOEP lifetime indicates differences in PtOEP aggregation in the polymer matrices. The presented results propose that the difference in the relative intensities of the delayed UC luminescence is determined by the difference between the ionization potentials of PtOEP and the polymer matrix. In the solid state, the electric-field-induced quenching of the delayed L5Ph UC luminescence suggests the formation of an intermediate charge-transfer state after the TTA within the PtOEP domains.
Keywords: Kinetics; Spectroscopy